Environmental governance and the dispersal of decision-making - Jenny Fairbrass (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
Currently the European Union (EU) consists of a group of nation states that exhibit an array of constitutional systems, ranging from the unitary to the fully federal. Among the EU member states, the United Kingdom (UK) has traditionally been regarded as an example par excellence of a unitary state. However, since taking office in the late 1990s, Labour Governments have pursued a programme of constitutional reform. This has included the decentral-isation of decision-making powers through a process of devolution to bodies in Scotland, Wales, Northern Ireland and the English Regions. One policy area that has been devolved as part of this process is environment policy. However, it could be argued that even before the formal 1998 Acts of devolution that environmental policy was already highly decentralised. Crucially though, one policy area that has been 'reserved' to the UK Executive in Whitehall and the Parliament in Westminster is international relations and EU matters, and UK environmental policy is one policy area that is deeply affected by EU level policy making. These circumstances, therefore, raise some important questions about British environmental governance, which this paper seeks to address. Crucially, what are the likely or potential implications of devolving environ-mental policy, whilst at the same time reserving EU relations to London (Whitehall and Westminster)? In reflecting on these issues, this paper draws on theories and concepts derived from governance and historical institutionalist literature.
Keywords: 330; Governance; UK policy making; devolution; European Union; environmental policy; Föderalismus; Umweltpolitik; Großbritannien; Politische Entscheidung; EU-Umweltpolitik